Pertemuan Spiritual di Ruang Digital: Studi Fenomenologis atas Interaksi Da’i dan Followers dalam Dakwah Islam - Tua Dalimunthe; Zilfaroni Zilfaroni (Ittishol: Jurnal Komunikasi dan Dakwah, 2025)
The rise of digital dakwah has transformed how Muslims experience and engage with religious communication. Social media platforms such as YouTube have become dynamic spaces where da’i (preachers) and followers construct new forms of spiritual interaction beyond physical gatherings. This study aims to explore the lived meanings of da’I follower interactions within digital preaching spaces, focusing on how spiritual experiences are mediated through online engagement. Employing an interpretative phenomenological approach, data were collected through the observation of 10–15 interactive YouTube preaching sessions and in-depth interviews with eight da’i and followers. The analysis followed Moustakas’ (1994) phenomenological procedure to uncover the essence of participants’ experiences. The findings reveal several key themes: digital intimacy, where followers feel emotionally and spiritually connected through the screen; mediated spirituality, in which faith experiences are shaped by technological presence; negotiated authority, reflecting the dialogic construction of religious legitimacy; and collective piety, expressed through shared emotions and rituals in live chat interactions. These themes illustrate that digital dakwah is not merely a form of religious broadcasting but a meaningful spiritual encounter enabled by technology. The study concludes that the digital sphere has become a new locus for Islamic spirituality and dakwah relations an interactive, participatory, and affective space where faith is collectively experienced and reinterpreted.